Prevalence and Factors Associated with Attention-Deficit Hyperactivity Disorder in Male Juvenile Delinquent of Metta Remand Home - Ketumarn, Panom; Hataiyusuk, Somboon; Pornnoppadol, Chanvit; Apinuntavech, Suporn (Journal of the Psychiatric Association of Thailand, 2016)
Objective: To evaluate the prevalence and associated factors of attention-deficit hyperactivity disorder (ADHD) in male juvenile delinquent of Metta Remand Home. Methods :This cross-sectional study examined 275 male adolescents, aged 11-18 years old, in male juvenile delinquent of Metta Remand Home between July 2012 and December 2013. Self-administered questionnaires were used to collect basic clinical characteristics and potential factors associated with ADHD. Then participants were screened for ADHD by using both self and parent versions of Thai ADHD screening scales (THASS). Finally, semi-structured interviews was performed by investigator among those adolescents with positive THASS results using ADHD section of Diagnostic Interview for Children and Adolescents-Revised (DICA-R) - Thai language. The prevalence rate of ADHD was reported. Statistical analyses were performed to compare factors in those subjects with and without ADHD diagnosis. Results :Of 275 male juvenile delinquent of Metta Remand Home, 31 (12.5%) were diagnosed with ADHD. Factors that were statistically associated with ADHD were employment status, use of illicit drugs other than alcohol or smoking, parental support and history of sexual harassment from community members. Conclusions :Prevalence of ADHD in male juvenile delinquent of Metta Remand Home is 12.5%, which is higher than general population. Factors associated with ADHD in this population need further investigation.